The Tetrodotoxin Receptor of Voltage-Gated Sodium Channels—Perspectives from Interactions with μ-Conotoxins - Baldomero M. Olivera; Michael F. Sheets; Robert J. French; Doju Yoshikami (Marine Drugs, 2010)
Neurotoxin receptor site 1, in the outer vestibule of the conducting pore of voltage-gated sodium channels (VGSCs), was first functionally defined by its ability to bind the guanidinium-containing agents, tetrodotoxin (TTX) and saxitoxin (STX). Subsequent studies showed that peptide μ-conotoxins competed for binding at site 1. All of these natural inhibitors block single sodium channels in an all-or-none manner on binding. With the discovery of an increasing variety of μ-conotoxins, and the synthesis of numerous derivatives, observed interactions between the channel and these different ligands have become more complex. Certain μ-conotoxin derivatives block single-channel currents partially, rather than completely, thus enabling the demonstration of interactions between the bound toxin and the channel’s voltage sensor. Most recently, the relatively small μ-conotoxin KIIIA (16 amino acids) and its variants have been shown to bind simultaneously with TTX and exhibit both synergistic and antagonistic interactions with TTX. These interactions raise new pharmacological possibilities and place new constraints on the possible structures of the bound complexes of VGSCs with these toxins.